Case report and literature analysis of ectopic gastric glands combined with intestinal-type gastric cancer in an HP-negative background - Peng, Shiyu; Tian, Shuxin (Frontiers in Oncology, 2025)
We report a rare case of intestinal-type gastric cancer combined with submucosal ectopic gastric glands in a patient without Helicobacter pylori (HP) infection. A 55-year-old female presented for a routine health check-up. Gastroscopy revealed a lesion approximately 2.0 cm in size, classified as type O-IIa+IIc, located on the posterior wall of the upper gastric body. Endoscopic biopsy indicated high-grade intraepithelial neoplasia, which promoted endoscopic submucosal dissection (ESD). Pathological examination confirmed mucosal adenocarcinoma with submucosal ectopic gastric glands. Given the association of such lesions with gastric cancer, careful diagnosis and treatment are essential. The patient remained disease-free without recurrence during a 2-year follow-up period.